INNOVATION AND INVESTMENT ANTI-CORRUPTION MECHANISM FOR ECONOMIC DEVELOPMENT - Yuldashev, O.; Smokovich, M.; Yuldashev, O.; Yuldashev, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It is substantiated that problems of the development of the mineral-raw material base of Ukraine (which, taking into account their importance, can be attributed to the fundamental geological problems of Eastern Europe), are problems of improving the management of this branch of the economy, the introduction of modern effective forms of management. This will ensure the energy independence of the country, its economic development, creation of additional jobs at the enterprises of the mineral complex and in related industries, and in the end - high standards of living of citizens. It is proved that the realization of potential opportunities for the further growth of existing stocks and exploration of new deposits for Ukraine, the extraction of which involves potential opportunities to achieve the country's energy and economic security, export potential increase, depends on solving a number of problems such as corruption (corruption in the extractive industry), insufficient volumes of exploration works, as well as a shortage of new technologies in mining. It is noted that these problems are associated with poor quality, inefficiency of management of the relevant branches of geology and mining (as well as the management of the country's economy as a whole). Solving these problems requires qualitative approaches, management tools, which are fundamentally different from the traditional methods of improving management. It is proposed to distinguish three types of such principles. First, it is the maximum reduction of the human factor, the transfer of such functions as control of the machines to the computers, the transition to new information technologies in management. Secondly, it is creation (to neutralize corruption risks from that part of the state apparatus, which is impossible to replace by the computer yet), of such organizational conditions, in which malversation of budget funds will become impossible. Thirdly, it is the application of the principle of subsidiarity in public administration. It is noted that one of the authors of this publication designed the desirable management system of the industry, as well as the model of transition from the current to the proposed management system is at the stage of registration of copyright to the utility model. It is emphasized that a particularly great effect, in the form of additional revenues to the budget, as well as relevant social transformations, will provide a widespread application of the proposed approach in reforming the entire state administration of the economy.
Keywords: mineral raw materials base; energy independence of the country; new technologies in mining; corruption in the mining industry; exploration of deposits; innovation and investment anticorruption mechanism of subsoil use; methods; principles; models of improvement of management